Physiological and metabolic responses of chemolithoautotrophic NO3− reducers to high hydrostatic pressure. Issue 6 (8th September 2022) - Pérez‐Rodríguez, Ileana; Sievert, Stefan M.; Fogel, Marilyn L.; Foustoukos, Dionysis I.
Abstract: We investigated the impact of pressure on thermophilic, chemolithoautotrophic NO 3 − reducing bacteria of the phyla Campylobacterota and Aquificota isolated from deep‐sea hydrothermal vents. Batch incubations at 5 and 20 MPa resulted in decreased NO 3 − consumption, lower cell concentrations, and overall slower growth in Caminibacter mediatlanticus ( Campylobacterota ) and Thermovibrio ammonificans ( Aquificota ), relative to batch incubations near standard pressure (0.2 MPa) conditions. Nitrogen isotope fractionation effects from chemolithoautotrophic NO 3 − reduction by both microorganisms were, on the contrary, maintained under all pressure conditions. Comparable chemolithoautotrophic NO 3 − reducing activities between previously reported natural hydrothermal vent fluid microbial communities dominated by Campylobacterota at 25 MPa and Campylobacterota laboratory isolates at 0.2 MPa, suggest robust similarities in cell‐specific NO 3 − reduction rates and doubling times between microbial populations and communities growing maximally under similar temperature conditions. Physiological and metabolic comparisons of our results with other studies of pressure effects on anaerobic chemolithoautotrophic processes (i.e., microbial S 0 ‐oxidation coupled to Fe(III) reduction and hydrogenotrophic methanogenesis) suggest that anaerobic chemolithoautotrophs relying on oxidation–reduction (redox) reactions that yield higher Gibbs energies experience larger shifts in cell‐specific respiration rates and doubling times at increased pressures. Overall, our results advance understanding of the role of pressure, its relationship with temperature and redox conditions, and their effects on seafloor chemolithoautotrophic NO 3 − reduction and other anaerobic chemolithoautotrophic processes.